Seroprevalence of toxoplasmosis, syphilis, hepatitis B, hepatitis C, rubella, cytomegalovirosis and human immunodeficiency virus infection among pregnant patients followed up from 2008 to 2012 at hospital universitário Antônio Pedro, Niterói RJ - Oliveira, Solange Artimos de; Vilte, Remberto Mauricio de la Cruz Vargas; Azevedo, Kátia Martins Lopes de; Setúbal, Sérgio (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Screening and treatment of infectious diseases in pregnant women have great importance in planning preventive actions and development of maternal and child health policies. Objective: To evaluate the seroprevalence of toxoplasmosis, syphilis, hepatitis B, hepatitis C, rubella, cytomegalovirosis and human immunodeficiency virus (HIV) infection among pregnant women followed up at a University Hospital of Niterói, RJ. Methods: A cross-sectional study was done by reviewing serological tests recorded in the medical records of pregnant women attending the antenatal service of the Hospital Antônio Pedro, Universidade Federal Fluminense, from 2008 to 2012. Results: The seroprevalences found were 61.4 (IgG) and 2.4% (IgM) for toxoplasmosis; 95.1 (IgG) and 0.5% (IgM) for rubella; 95.1 (IgG) and 1.2% (IgM) for cytomegaloviruosis; 0.9% for hepatitis B surface antigen; 1.6% for hepatitis C virus; 1.5% for syphilis and 5.8% for HIV infection. There were no statistically significant differences between seroprevalences of patients with or without HIV infection. The rates of congenital transmission were 4.2% (2/48) for HIV, 33.3% (5/15) for toxoplasmosis, and 22.2% (2/9) for syphilis. There were congenital abnormalities in 1/5 newborn whose mother was seropositive for rubella IgG and/or IgM in the prenatal routine. Coinfection HIV/toxoplasmosis was found in one newborn. Conclusion: The large proportion of pregnant women susceptible to toxoplasmosis (38.8%) and hepatitis B (66.3%) shows the necessity of diagnostic and preventive measures for toxoplasmosis and HBV vaccination to reduce the risk of vertical transmission of these infections, thus improving the health of mother and newborn.